Integration and Application of Microlens Arrays Within Heads-Up Displays - Weicheng Yan; Xian Jin; Hongbae S. Park; Ashli Le Blanc; Hamid Abdollahi; Boris Stoeber; Jonathan F. Holzman (IEEE Photonics Journal)
The proposed work targets a fundamental challenge in heads-up display technology—in that such displays must bring about tight imaging with a flat form factor to support integration within eyewear. A Gabor superlens, being coupled plano-concave and plano-convex microlens arrays (MLAs), is developed to meet this challenge. The MLAs are designed and optimized, via tradespace analyses and ray-based simulations, and then formed with a specialized fabrication process. The process applies plasma pretreatment to the substrate followed by dispensing, curing, and casting of microlenses on the substrate to realize arrays with the necessary diameters and radii of curvature. The plano-concave and plano-convex MLAs are coupled to form the superlens, which is packaged with a baffle and microdisplay to function as the heads-up display. Ray-based simulations and experimental characterizations are carried out on the modulation transfer function of the display to define its resolution. It is found that the superlens can bring about strong imaging performance—with a resolution of up to 30 cycles/mm—as well as the tight imaging and flat form factor that are needed for emerging heads-up display technologies.